THE EFFECT OF PEAT SWAMP WATER ON TOOTH DEMINERALIZATION OF COPPER AND SELENIUM ION - Muhammad Rizki Ridho; Dewi Puspitasari; I Wayan Arya Khrisnawan Firdaus (FKG Unlam, 2020)
ABSTRACTBackground: The society of South Kalimantan has high rate of tooth decay. The high rate of tooth decay in South Kalimantan is caused by environmental factors, namely water sources originating from peat swamp. Swamp water has acidic pH can make tooth demineralization or releasing minerals in tooth. One of the minerals that can be demineralized by swamp water is copper ions (Cu2+) and selenium ions (Se4+). The released minerals in tooth makes tooth enamel slowly dissolve and make tooth more susceptible to caries. Objective: to analyze the effect of tooth immersion on peat swamp water on releasing copper and selenium ions. Methods: This research used a laboratory experimental study with eighteen specimens of extracted human maxillary premolar teeth. The specimens were divided into 2 treatment groups ie tap (PDAM) water and peat swamp water immersion, and 1 control group ie artificial saliva immersion. Tooth immersion is conducted for 7 days. The Measurement of copper and selenium ions release using a UV-Vis spectrophotometer. Data were statistically tested using One Way Anova. Result: The mean value of released copper ions in artificial saliva (3.8 ± 0.51 ppm), tap water (3.72 ± 1.02 ppm) and peat swamp water (3.37 ± 0.97 ppm) showed there were no significant differences among all immersion groups. Meanwhile, the mean value of released selenium ions in artificial saliva (7.61 ± 2.34 ppm), tap water (2.4 ± 0.62 ppm) and peat swamp water (0.85 ± 0,38 ppm) showed there were significant differences among all immersion groups on the release of selenium ions, subsequenty test using Post hoc Dunnett's T3 showed p=0.0001 (p<0.05). Conclusion: There is no effect of tooth immersion in peat swamp water on the release of copper ions however there is an effect on the release of selenium ions.Keywords: Demineralization, Peat swamp water, Releasing copper ions (Cu2+), Releasing selenium ions (Se4+), tooth decay.